2018
DOI: 10.1111/jcmm.13990
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of soluble ST2, but not IL‐33, correlate with the severity of alcoholic liver disease

Abstract: Alcoholic liver disease (ALD) is a complication that is a burden on global health and economy. Interleukin‐33 (IL‐33) is a newly identified member of the IL‐1 cytokine family and is released as an “alarmin” during inflammation. Soluble suppression of tumourigenicity 2 (sST2), an IL‐33 decoy receptor, has been reported as a new biomarker for the severity of systemic and highly inflammatory diseases. Here, we found the levels of plasma sST2, increased with the disease severity from mild to severe ALD. Importantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…A study with patients positively correlated the soluble suppression values of tumorigenesis-2 (sST2) with IL-6, IL-1β, the severity of the Child–Pugh scale, and the Maddrey test score used to discriminate the severity of alcoholic hepatitis. Interestingly, this study did not show an elevation in IL-33 levels [ 117 ]; IL-33 is the ligand of ST2. It should be noted that the measurement of sST2 is postulated to be a prognostic biomarker in heart failure [ 118 ].…”
Section: Alcohol Use Disordermentioning
confidence: 78%
“…A study with patients positively correlated the soluble suppression values of tumorigenesis-2 (sST2) with IL-6, IL-1β, the severity of the Child–Pugh scale, and the Maddrey test score used to discriminate the severity of alcoholic hepatitis. Interestingly, this study did not show an elevation in IL-33 levels [ 117 ]; IL-33 is the ligand of ST2. It should be noted that the measurement of sST2 is postulated to be a prognostic biomarker in heart failure [ 118 ].…”
Section: Alcohol Use Disordermentioning
confidence: 78%
“…Accumulating evidence has shown that circulating sST2 not only has a relationship with cardiovascular diseases, including acute myocardial infarction (MI) [ 15 ], pulmonary hypertension [ 20 ], coronary artery disease [ 27 ] and heart failure [ 21 , 22 ] but also plays a role in many other systemic diseases, including asthma [ 28 ], obesity [ 29 ], type 2 diabetes [ 30 ], diabetic kidney disease [ 31 ], tumor [ 32 ], alcoholic liver disease [ 33 ], and Alzheimer’s disease [ 34 ]. Most often, sST2 involvement appeared to be better predictive than IL-33 due to its higher levels and stability.…”
Section: Discussionmentioning
confidence: 99%
“…In human patients with alcoholic liver disease, sST2 but not IL-33 was correlated to the severity of the disease (88). In the same fashion, Wang et al (89) showed with IL-33- and ST2- deficient mice that ST2 decreases the inflammatory activation of hepatic macrophages by inhibiting NF-κB in alcoholic liver disease, in an IL-33-independent manner.…”
Section: Contribution Of Il-1 Superfamily Of Cytokines To Hepatic Dismentioning
confidence: 99%